(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article provides a comprehensive overview of sound alternations, a key concept in phonology that explains systematic variations in pronunciation within languages. It begins by defining sound alternations and describing how they manifest through various types, such as assimilation, dissimilation, insertion, deletion, lenition, fortition, vowel harmony, and metathesis. The article highlights the motivations behind sound alternations, including ease of articulation, rhythmic flow, morphological rules, and historical language changes. By presenting examples from languages like English, Spanish, Japanese, and Turkish, the article illustrates the universality and diversity of these phonological processes. In the conclusion, the article emphasizes the significance of sound alternations in facilitating smooth, efficient communication and shaping linguistic evolution over time. An additional conclusion underscores how these alternations reveal insights into broader linguistic principles and historical language shifts, offering valuable perspectives on how languages adapt to meet the needs of their speakers. This article serves as a useful resource for linguistics students, language enthusiasts, and anyone interested in understanding the subtle yet powerful role of sound patterns in human language.